Propagation Model for Ground-to-Aircraft Communications in the Terahertz Band with Cloud Impairments - Vladimir Doborshchuk; Vyacheslav Begishev; Konstantin Samouylov (Energies, 2022)
By operating over a large bandwidth, the terahertz (THz) frequency band (0.3–3 THz) promises to deliver extremely high data rates. While the use of this band in cellular communications systems is not expected to happen within the next decade, various other use-cases such as wireless backhauling and point-to-point wireless access are on the immediate horizon. In this study, we develop an analytical propagation model for the case of ground-to-aircraft communications by explicitly accounting for THz-specific propagation phenomena including path loss, attenuation by different types of clouds, and atmospheric absorption at different altitudes. To this aim, we first exhaustively characterize the geometric, molecular, and structural properties of clouds for different weather conditions and Earth regions. Then, by applying the tools of stochastic geometry, we present the closed-form expression for received power at the aircraft. Our numerical results show that the type of weather forming different compositions of clouds provides a major impact on the overall path losses and thus the attained data rates. Specifically, the difference between sunny and rainy conditions may reach 30–50 dB. The overall path loss also heavily depends on the region time and the difference may reach 10–30 dB. The worst conditions are logically provided by rain, where the additional attenuation on top of sunny conditions reaches 50 dB over the whole THz band. The Middle Earth zone is also the worst out of the considered regions with additional attenuation reaching 30 dB. The developed model can be used as a first-order approximation for ground-to-aircraft THz channel modeling.